Left atrial function evaluation by 2D speckle‐tracking echocardiography in patients with vasovagal syncope - Tajdini, Masih; Hosseinsabet, Ali; Tofighi, Saeed; Yadangi, Somayeh (Pacing and clinical electrophysiology, 2023)
Objectives Evidence indicates left atrial (LA) involvement in vasovagal syncope (VVS). The LA regulates left ventricular filling during the cardiac cycle. We aimed to assess LA function in patients with VVS by 2D speckle‐tracking echocardiography. Methods Sixty‐nine consecutive patients with VVS were recruited. Based on the head‐up tilt test (HUTT) results, the study population was divided into two groups: HUTT+ (n = 45) and HUTT− (n = 24). Fifty‐one consecutive subjects were enrolled as the control group. LA myocardial deformation parameters were measured by 2D speckle‐tracking echocardiography to evaluate LA function. Results Maximal, minimal, and pre‐P LA volumes were lower in patients with VVS. Strain and strain rate during reservoir, conduit, and contraction phases in VVS patients with HUTT+ or HUTT− were not statistically significantly different from those in the control group. Additionally, the volumetric parameters of LA function showed no difference in statistical significance between the three study groups. Conclusions While LA phasic function was not different between the two groups of VVS patients with HUTT+ or HUTT− and the control group, LA size during the three LA phases was smaller in patients with VVS.